The Portrayal of the Eldest Daughter in the Song “Eldest Daughter” By Taylor Swift - Alifya Zafira Subakti; Khaerudin Imawan (CV. Syntax Corporation Indonesia, 2026)
Popular music is a strategic medium for cultural communication that conveys emotions and ideology, social values, and the construction of gender identity. Taylor Swift's song